Agribusiness Innovation Research Trends Based on Scopus Database for the Period 2013–2024 - Loso Judijanto (West Science Agro, 2026)
This study aims to map the research trends on agribusiness innovation indexed in the Scopus database during the period 2013–2024 using a bibliometric approach. Data were collected from Scopus and analyzed using VOSviewer to examine publication growth, co-authorship networks, institutional and country collaborations, as well as keyword co-occurrence and thematic evolution. The findings indicate a significant increase in publications over the last decade, reflecting growing academic attention to agribusiness innovation. The keyword network reveals that agribusiness functions as the central theme, closely linked to sustainable development, food security, agroindustry, and agricultural economics. Overlay visualization shows a recent shift toward digital transformation topics such as internet of things (IoT), big data, and smart agriculture, highlighting the increasing integration of Industry 4.0 technologies within agricultural systems. Collaboration analysis identifies Brazil, India, the United States, and several European countries as major contributors to the global research network. The study demonstrates that agribusiness innovation research has evolved from a productivity-oriented perspective toward a systemic, sustainability-driven, and technology-enabled paradigm. These findings provide a comprehensive overview of the intellectual structure and future research directions in agribusiness innovation.